2021
DOI: 10.3389/fphar.2021.719308
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Liver Disturbance During the Treatment of COVID-19

Abstract: An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurred in Wuhan, China, at the end of 2019. The World Health Organization named the resulting infectious disease as coronavirus disease-2019 (COVID-19). Many studies concluded that patients infected with SARS-CoV-2 have different degrees of liver disturbance. However, the relationship between the drugs used for COVID-19 treatment and liver disturbance remains controversial. It is essential to evaluate the potential liver damage cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
0
13
0
4
Order By: Relevance
“… 9 , 18 Although cases of AKI and increased aminotransferase level have been reported for treating COVID‐19, even among healthy volunteers, many randomised controlled studies have demonstrated limited adverse events with an acceptable safety profile. 9 , 11 , 12 , 13 , 14 , 15 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 , 18 Although cases of AKI and increased aminotransferase level have been reported for treating COVID‐19, even among healthy volunteers, many randomised controlled studies have demonstrated limited adverse events with an acceptable safety profile. 9 , 11 , 12 , 13 , 14 , 15 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…9,18 Although cases of AKI and increased aminotransferase level have been reported for treating COVID-19, even among healthy volunteers, many randomised controlled studies have demonstrated limited adverse events with an acceptable safety profile. 9,[11][12][13][14][15][19][20][21] In brief, kidney and liver injury are reported shortly after remdesivir initiation in case studies, 9,[22][23][24] but the exact injury mechanisms remain to be defined and investigated. Controlled trials may find remdesivir to be generally tolerable, [25][26][27] yet its safety data on AKI and acute liver injury (ALI) in the post-marketing real-world setting have not been published so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manifestations of SARS-CoV-2 infection mainly include fever, fatigue, and dry cough [5]. Some patients present symptoms, including runny nose, sore throat, nasal congestion, and diarrhea [6]. Those with severe symptoms usually present dyspnea and hypoxemia one week after the disease appear.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article [ 32 ], it was stated that it is important to evaluate the potential liver damage caused by various drugs in order to help guide clinical practice. In this review, these treatments were associated with minimal liver function abnormalities, but it is very important to pay attention to multimedication.…”
Section: Discussionmentioning
confidence: 99%